The Finance-Growth Nexus in South Africa - McHardy, Gareth (School of Economics, 2023)
The finance-growth nexus remains a divisive topic within macroeconomic discourse. Despite the plethora of studies devoted to understanding the causal relationships, there is still vast disagreement. This study comprehensively examines the relationship between economic growth, financial development and financial structure within the South African context from 1980-2020. The parsimonious and theoretically-grounded Solow growth model specifications are estimated using the auto-regressive distributed lag (ARDL) approach to co-integration. Five alternative specifications that employ one measure of financial development or financial structure at a time are tested. The results are ambiguous. When proxied by the liquid liabilities ratio, financial development is found to have positively contributed to long-run and short-run economic growth in the country. Conversely, when the private credit ratio is used, financial development becomes insignificant. South Africa's financial development certainly has no negative effects on the country's growth prospects – a conclusion that carries important policy implications. In terms of financial structure, both the stock market value traded ratio and the stock market capitalisation ratio, yield insignificant results, lending itself to the conclusion that financial structure does not matter. Lastly, a composite financial development indicator was used to see whether financial inclusion has bearing on the relationship. The result is insignificant but given the nature of the indicator, financial inclusion is not rendered irrelevant. If pro-poor growth remains the objective of the South African government, the financial sector has an important role to play in promoting growth and reducing inequality. Furthermore, it remains imperative to strengthen financial institutions in ways that ameliorate current imbalances. As a final remark, there is no economic value in promoting one financial structure over the other and financial development can be growth-enhancing provided the sector is adequately regulated with consistent policy